Pengaruh Umur Beranak Pertama Terhadap Performa Produksi Susu Sapi Friesian Holstein di BBPTU-HPT Baturraden - Awan, J.S.; Atabany, A.; Purwanto, B.P. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2016)
The objective of this study was to observe effect of first cavling Friesian Holstein age on milk yield performance at BBPTU-HPT Baturraden. This study was conducted using 150 sets of weekly recording of milk yield from 350 Friesian Holstein cows. Milk yield was calculated by using time interval method (TIM) which was equvalent to ME 305 days. The data were analysed using polynomial regression model. Result of the study indicated that BBPTU-HPT has made efforts to improve the age first calving, but has an impact on longer day open and shorter period of lactation with longer dry period so that calving interval has been longer than what’s been indicated not efficient and optimal. The age first calving significant through milk yield followed the pattern of linear regression